1996
DOI: 10.1074/jbc.271.24.14376
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Cholesterol-lowering Drug SR-12813 Inhibits Cholesterol Synthesis via an Increased Degradation of 3-Hydroxy-3-methylglutaryl-coenzyme A Reductase

Abstract: SR-12813 (tetra-ethyl 2-(3,5-di-tert-butyl-4-hydroxyphenyl)ethenyl-1, 1-bisphosphonate) lowers plasma cholesterol in five species. In this paper we investigate the underlying mechanism using Hep G2 cells. SR-12813 inhibited incorporation of tritiated water into cholesterol with an IC50 of 1.2 microM but had no effect on fatty acid synthesis. Furthermore, SR-12813 reduced cellular 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase activity with an IC50 of 0.85 microM. The inhibition of HMG-CoA reductase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…This is consistent with the observed targeting of alendronate to the osteoclast and not the osteoblast or bone marrow cells [6,8]. The decline in HMG-CoA reductase expression is consistent with earlier observations showing that the bisphosphonate SR-12813 induces degradation of HMG-CoA reductase [25], which is mediated through an unknown mechanism. The effect observed in the osteoclast appeared to be mediated, in part, by the accumulation of metabolites upstream of the BP-inhibited enzyme FPP synthase, because coadministration of simvastatin, along with alendronate, partially blocked the effect.…”
Section: Evidence For Bisphosphonate Mechanism Of Action In Vivosupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with the observed targeting of alendronate to the osteoclast and not the osteoblast or bone marrow cells [6,8]. The decline in HMG-CoA reductase expression is consistent with earlier observations showing that the bisphosphonate SR-12813 induces degradation of HMG-CoA reductase [25], which is mediated through an unknown mechanism. The effect observed in the osteoclast appeared to be mediated, in part, by the accumulation of metabolites upstream of the BP-inhibited enzyme FPP synthase, because coadministration of simvastatin, along with alendronate, partially blocked the effect.…”
Section: Evidence For Bisphosphonate Mechanism Of Action In Vivosupporting
confidence: 92%
“…In vivo testing showed that certain compounds suppressed serum cholesterol in rodents, although alendronate had little effect [20,23], likely because of its specific targeting to bone. Other cholesterol-lowering bisphosphonates triggered degradation of hydroxymethylglutaryl coenzyme A, which is the target of the statins [24,25]. In the same context, squalene synthase inhibition by bisphosphonate was also used for the development of an assay to measure zoledronate levels in animals and clinical serum samples [26].…”
Section: Actions At the Molecular Levelmentioning
confidence: 99%
“…In particular, the enzyme is degraded within a few hours when cells are treated with large amounts of 25-hydroxycholesterol (13,20,21). One action of this regulatory oxysterol is to rapidly increase the level of ER cholesterol (9), thereby priming HMGCoAR for homeostatic down-regulation (13).…”
Section: Resultsmentioning
confidence: 99%
“…A representative of this class of compounds, SR-12813, has been shown to inhibit the MVA pathway in HepG2 cells by increasing the rate of HMGR degradation (54). The resulting decrease in cholesterol synthesis, which was also observed in vivo in dogs that were orally administered with SR-12813, leads to hypocholesterolemia.…”
mentioning
confidence: 99%